Phylogenetic placement of the enigmatic genus Holocheila (Lamiaceae) inferred from plastid DNA sequences. Issue 2 (17th March 2014) - Chen, Ya-Ping; Li, Bo; Olmstead, Richard G.; Cantino, Philip D.; Liu, En-De; Xiang, Chun-Lei
Abstract: The monotypic genus Holocheila was originally placed in Teucrium sect. Holocheila but was later treated as a distinct genus and variably affiliated with subfamilies Ajugoideae, Scutellarioideae, or Lamioideae. We investigated the phylogenetic position of this enigmatic genus using likelihood, parsimony, and Bayesian methods based on six plastid DNA sequences. The preliminary results from a concatenated ndhF and rbcL dataset that covered all seven subfamilies of Lamiaceae suggested that Holocheila is part of subfamily Lamioideae. To examine its position within Lamioideae more thoroughly, a dataset was assembled that included representatives of 59 of the 63 genera of Lamioideae and data for four genetic markers: trnL intron, trnL‐trnF spacer, rps16 and matK . The results showed that Holocheila is part of tribe Pogostemoneae. Glossy mericarps and unilocular anthers are apomorphies that Holocheila shares with some members of Pogostemoneae. The genera Acrymia and Cymaria, which have been considered incertae sedis, were found to be the closest relatives of Lamioideae. Four other incertae sedis genera ( Garrettia, Hymenopyramis, Peronema, Petraeovitex ) appear to form a clade that is sister to the clade comprising Lamioideae, Acrymia, Cymaria, and Scutellarioideae.